Nuttall’s species of Sphaeromeria transferred to Artemisia (Asteraceae): a new combination and comments on typifications - Mosyakin, Sergei L.; Shultz, Leila M.; Boiko, Ganna V. (Phytotaxa, 2017)
Following recent molecular phylogenetic studies, the genus Sphaeromeria has been synonymized with Artemisia and its taxa are included in Artemisia subg. Tridentatae. The new combination is proposed, Artemisia nuttallii (Torr. & A. Gray) Mosyakin, L.M. Shultz & G.V. Boiko, comb. nov. (= Sphaeromeria argentea Nutt., non A. argentea L’Her.; Tanacetum nuttallii Torr. & A. Gray; Artemisia macarthuri Sòn. Garcia et al., nom. illeg.). Notes on typifications of the names Sphaeromeria argentea and S. capitata Nutt. (now Artemisia capitata (Nutt.) Sòn. Garcia et al.) are provided; both are typified by Nuttall’s specimens from BM. Additional original specimens of these two species recently found in the Turczaninow memorial collection at the National Herbarium of Ukraine (KW) are discussed.